Strategi Pengembangan Masyarakat: Alternatif Pemikiran Reformatif - Tadjudin Nur Effendi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1999)
This article briefly discusses an alternative strategy to develop enteurpreneurship of rural communities which is considered as an important part of human resources development. The main problem in the development of human resources is not only to improve people's education but also to develop their enteurpreneurship. This strategy could he achieved by shifting the paradigm of development from planned (top down) towards etno development (bottom up). By this, the focus of rural development is to develop economic activities which is based on a self supporting of rural communities. It is suggested that the existing of rural community enterprises that have been neglected in the past years, have to give priority in rural development process in the future years. The advantage of this approach is not only able to improve welfare of rural communities but also to form learning community (social learning) which is an important process in composing the enterpreneurship of rural communities.